Slenderness Ratio and Influencing Parameters on the NL Behaviour of RC Shear Wall - A. Atmani; Z. Boudaoud; N. Djebbar (Civil Engineering Journal, 2021)
Shear walls are very efficient structural elements to resist lateral seismic disturbance. Despite the aforementioned seismic performance, recent investigations report that they have suffered from significant structural damage after recent seismic activity, even for those complying with seismic provisions. These deficiencies in resistance and deformation capacities need to be explored. This study considers the influence of plastic length Lp, concrete compressive strength f_c28, longitudinal reinforcement ratio ρl, transverse reinforcement ratio ρsh, reduced axial load ν, confinement zone depth CS and focusing on the geometric slenderness λ. The parametric study has been conducted through NL pushover analysis using Peform3D software. The chosen coupled shear-flexure fiber macro model was calibrated with well-known cyclic experimental specimens. The paper points out the discrepancy between the two well-known codes EC8 and ASCE/SEI 41-13. In fact, the value of the slenderness ratio (λ) that trigger the beginning of a purely flexural behaviour recommended by EC8 (λ>2) is very different from the value of the ASCE/SEI 41-13 (λ>3) without accounting for the effect of the reduced axial force. Finally, it was found that RCW capacities are very sensitive to f_c28, ν, ρl, Lp and less sensitive to ρsh and CS. However, (λ) is the most decisive factor affecting the NL wall response. A new limit of slenderness and appropriate deformations of rotations are recommended to provide an immediate help to designers and an assistance to those involved with drafting codes. Doi: 10.28991/cej-2021-03091777 Full Text: PDF